2016
DOI: 10.1186/s12864-016-2588-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel strain of cynomolgus macaque cytomegalovirus: implications for host-virus co-evolution

Abstract: BackgroundCytomegaloviruses belong to a large, ancient, genus of DNA viruses comprised of a wide array of species-specific strains that occur in diverse array of hosts.MethodsIn this study we sequenced the ~217 Kb genome of a cytomegalovirus isolated from a Mauritius cynomolgus macaque, CyCMV Mauritius, and compared it to previously sequenced cytomegaloviruses from a cynomolgus macaque of Filipino origin (CyCMV Ottawa) and two from Indian rhesus macaques (RhCMV 180.92 and RhCMV 68–1).ResultsThough more closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…While RhCMVs and CyCMVs are closely related to each other, they still clustered separately according to the host species. Our novel RhCMV isolates were grouped with the RhCMV laboratory strains 68–1 and 180.92, whereas all of our MCM CyCMV isolates were closely aligned with the recently published isolate CyCMV Mauritius [19] and demonstrated a close sequence relationship to CyCMV Ottawa, an isolate derived from a Filipino-origin CM [9]. Thus, we have successfully isolated seven novel RhCMV and MCM CyCMV from animals housed at ONPRC.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…While RhCMVs and CyCMVs are closely related to each other, they still clustered separately according to the host species. Our novel RhCMV isolates were grouped with the RhCMV laboratory strains 68–1 and 180.92, whereas all of our MCM CyCMV isolates were closely aligned with the recently published isolate CyCMV Mauritius [19] and demonstrated a close sequence relationship to CyCMV Ottawa, an isolate derived from a Filipino-origin CM [9]. Thus, we have successfully isolated seven novel RhCMV and MCM CyCMV from animals housed at ONPRC.…”
Section: Resultssupporting
confidence: 63%
“…Here, we have increased our understanding of RhCMV and CyCMV by isolating and sequencing three new RhCMV strains derived from Indian-origin rhesus macaques born and housed at the ONPRC, and four CyCMV isolates derived from cynomolgus macaques originally born on the island of Mauritius. Only two CyCMV strains had been described prior to our present analysis, one from a Filipino-origin and the other from a Mauritius-origin CM [9,19]. Unfortunately, neither strain was full-length and both carried deletions of their RL13 homologue and adjoining regions of the genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the phylogenetic trees of primate cytomegaloviruses and their hosts' were compared, and primate cytomegalovirus genomes were also analysed. The obtained results demonstrated the coevolution of these viruses with their hosts (Russell et al 2016). Furthermore, the avian and reptilian HVs were clustered into the subfamily Alphaherpesvirinae, relating to the development of birds from reptilian progenitors (McGeoch and Gatherer 2005).…”
Section: Herpesvirusesmentioning
confidence: 67%
“…CMVs display remarkable species-specificity, which results from long-term co-evolution with and adaptation to their mammalian hosts [13,14]. Comparison of the HCMV genome with those of non human primate-infecting CMVs indicated that duplication and gene copy number variation of non-core genes were common during CMV evolution and probably contributed to host adaptation [1,10].…”
Section: Introductionmentioning
confidence: 99%